The water paradox: scarce and valuable but inefficient use and poo political decisions - who should we blame? - Carruthers J. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
Water is now scarce and valuable but those who command the bulk of its use still waste too much of it and those politicians who could reallocate it to higher value uses are poorly briefed by their technical advisers. It is argued that economics has an important but strictly limited role to play in setting options for choice. All civil society, and perhaps especially the professional societies and universities, have a crucial role to play in creating and assessing alternatives and in guiding political choice
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)